Pathophysiology of trauma-induced coagulopathy: disseminated intravascular coagulation with the fibrinolytic phenotype - Hayakawa, Mineji (J Intensive Care, 2017)
In severe trauma patients, coagulopathy is frequently observed in the acute phase of trauma. Trauma-induced coagulopathy is coagulopathy caused by the trauma itself. The pathophysiology of trauma-induced coagulopathy consists of coagulation activation, hyperfibrino(geno)lysis, and consumption coagulopathy. These pathophysiological mechanisms are the characteristics to DIC with the fibrinolytic phenotype.